A faithful interpreter? Li Zibiao and the 1793 Macartney embassy to China - Harrison, H (Routledge, 2018)
This paper is about the interpreter of the first British embassy to China. Li Zibiao was a Chinese Catholic priest who Lord Macartney recruited in Europe and brought with him to China. This account of his participation in the embassy aims to help us understand the role of the interpreter in intercultural negotiations in the late 18th century. Interpreting is something we tend to think of as invisible, but in these negotiations, where only a single interpreter was present, the interpreter had significant power. In effect, he acted as a mediator, shuttling between the two parties to enable each to accept the positions of the other so that the negotiations could come to a more or less successful conclusion. This position of power meant that the interpreter’s own institutional and personal interests could also be important to the negotiations. Thus loyalty was crucial to how interpreting worked. Li’s achievement during the negotiations was to create a situation where both Lord Macartney and the Qing officials were willing to accept him as a mediator and where he survived to tell the tale.